Manfaat Emotional Intelligence Bagi Pengajar dalam Proses Belajar Mengajar - Astrini, Astrini (Bina Nusantara University, 2010)
This paper contains a theoretical overview of Emotional Intelligence or emotional intelligence that can be applied in teaching and learning. The application of emotional intelligence is not only beneficial to create quality graduates but is also useful for self-development of teachers. Emotional intelligence can be developed by the faculty including the development of self-awareness of their feelings experience, acceptance and management of feelings, relationships built with students and also the ability to create a conducive learning environment for students ready to learn.